Distribuição espacial da lagarta-do-cartucho, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), na cultura do milho - Farias, Paulo R. S.; Barbosa, José C. [UNESP]; Busoli, Antônio C. [UNESP] (My University, 2001)
The spatial distribution of Spodoptera frugiperda (J.E. Smith) on corn is essential to perform control strategies, to improve sample technics, to estimate economic losses and incorporate spatial dynamics within population models. Experiments were carried out in three fields, each one composed of 100 plots, where 10 plants per plot were sampled at random, totalizing 1,000 plants per field in five sampling dates. The number of small caterpillars (shorter than 10 mm) and large ones (longer than 10 mm) per plant was counted. The negative binomial distribution model fitted well for small caterpillars, indicating that this larval stage is aggregated in these fields. For large caterpillars the model showed a moderate fit, and some dates adjusted well to the Poisson distribution. Thus, the small caterpillars (high populational density) show an aggregated distribution in the field, whereas the large ones (low populational density) could be more dispersed, tending to an at random distribution.
Spatial distribution of the fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), on corn crop
Keywords: Dispersion indices; Insecta; Spatial distribution; Zea mays